Adjacent segment disease and C-ADR: promises fulfilled? - Riew, K Daniel; Schenk-Kisser, Jeannette M; Skelly, Andrea C (Evidence-Based Spine-Care Journal, 2012)
Study design: Systematic review.Clinical question: Do the rates and timing of adjacent segment disease (ASD) differ between cervical total disc arthroplasty (C-ADR) and anterior cervical discectomy and fusion (ACDF) in patients treated for cervical degenerative disc disease? Methods: A systematic search of MEDLINE/PubMed and bibliographies of key articles was done to identify studies with long-term follow-up for symptomatic and/or radiographic ASD comparing C-ADR with fusion for degenerative disc disease of the cervical spine. The focus was on studies with longer follow-up (48–60 months) of primary US Food and Drug Administration trials of Prestige ST, Prodisc-C, and Bryan devices as available. Trials of other discs with a minimum of 24 months follow-up were considered for inclusion. Studies evaluating lordosis/angle changes at adjacent segments and case series were excluded. Results: From 14 citations identified, four reports from three randomized controlled trials and four nonrandomized studies are summarized. Risk differences between C-ADR and ACF for symptomatic ASD were 1.5%–2.3% and were not significant across RCT reports. Time to development of ASD did not significantly differ between treatments. Rates of radiographic ASD were variable. No meaningful comparison of ASD rates based on disc design was possible. No statistical differences in adjacent segment range of motion were noted between treatment groups. Conclusion: Our analysis reveals that, to date, there is no evidence that arthroplasty decreases ASD compared with ACDF; the promise of arthroplasty decreasing ASD has not been fulfilled.